Cambodia Rural Water Supply and Sanitation Sector Improvement Support : Synthesis Report - World Bank (2016)
This synthesis report documents the implementation process, results and lessons learned under a three-year Technical Assistance (TA) program undertaken by the Water and Sanitation Program of the World Bank’s Water Global Practice (WSP) in Cambodia between May 2013 and June 2016. It also presents recommendations for the government on key steps to accelerate service delivery at scale for Rural Water Supply, Sanitation and Hygiene (RWSSH) and for the World Bank to strategically engage in the sector. For comprehensiveness, annexes are attached that include key supporting documentation, and resources and deliverables developed under this TA are also provided in the resource pack (the resource pack is linked to Box folder which is available upon request).